Bulky bracelet jewellery: Inspired by Malaysian batik / Muhammad Haikal Abdul Hamid - Abdul Hamid, Muhammad Haikal (2022)
Malaysian batik is batik textile art in Malaysia, especially on the east coast of Malaysia (Kelantan, Terengganu and Pahang). The most popular motifs are leaves and flowers. Malaysian batik depicting humans or animals are rare because Islam norms forbid animal images as decoration. Bulky bracelet definition using the most used terminology and definitions for related terms.